(untitled) (Marketing Journal, 2025)
The article studies the role and importance of financial relations in ensuring the stability of the activities of small business entities. The levels of financial and capital stability of small business entities in the Andijan region are analyzed. The leve l of stability of loans to small business entities in the territories of Andijan region was evaluated based on the ratio per capita and the ratio to small business entities.